2008
DOI: 10.1103/physreve.77.041607
|View full text |Cite
|
Sign up to set email alerts
|

Rate equations and scaling in pulsed laser deposition

Abstract: We study a simplified model for pulsed laser deposition [Hinnemann, Phys. Rev. Lett. 87, 135701 (2001)] by rate equations. We consider a set of equations where islands are assumed to be pointlike, as well as an improved one that takes the size of the islands into account. The first set of equations is solved exactly but its predictive power is restricted to a few pulses. The improved set of equations is integrated numerically, is in excellent agreement with simulations, and fully accounts for the crossover fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Based on the results, it was concluded that logarithmic data collapsing was accidental. Very recently, Barato, Hinrichsen, and Wolf carried out rate equation analysis on the nucleation density, and it was found that the scaling was not logarithmic in their analysis [32]. Therefore, although data appear to collapse in Fig.…”
Section: A Scaling Of Nucleation Density For Pldmentioning
confidence: 98%
“…Based on the results, it was concluded that logarithmic data collapsing was accidental. Very recently, Barato, Hinrichsen, and Wolf carried out rate equation analysis on the nucleation density, and it was found that the scaling was not logarithmic in their analysis [32]. Therefore, although data appear to collapse in Fig.…”
Section: A Scaling Of Nucleation Density For Pldmentioning
confidence: 98%
“…5), that is, the number and size of islands are distributed differently. In addition, the islands should remind us of fractal objects in both cases and their fractal dimension can be approximately calculated within the diffusion limited aggregation (DLA) model [30]. The system equations as Eqs.…”
Section: Debris Recrystallization Process Described By Meanmentioning
confidence: 99%
“…The time evolution density quantification for such surface structures in the presence of a timedependent rate flux can be written using a system of two relatively simple equations: the total number of growing clusters, x(t) and the density of clusters of size 1 adatoms, y(t). The time-dependent equations for the x(t) (that can be considered the nucleation density, the aggregation of more than two clusters is excluded) and y(t), the system equations in dimensionless form are written as follows [21,30]:…”
Section: Debris Recrystallization Process Described By Meanmentioning
confidence: 99%
“…[120][121][122] However, nucleation in pulsed deposition is not as easily analyzed in the framework of rate equations as integration cannot be performed when the flux is discontinuous. [123] Instead, the general scaling behaviors of given by Eq. 8 and Eq.…”
Section: Nucleation and Island Growth In Pulsed Depositionmentioning
confidence: 99%